2008
DOI: 10.1038/cgt.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric form of tumor necrosis factor-α has enhanced surface expression and antitumor activity

Abstract: Tumor necrosis factor (TNF)-a is a type-II transmembrane protein that is cleaved by TNF-a-converting enzyme (TACE/ADAM-17) to release soluble TNF, a cytokine with potent antitumor properties whose use in clinical applications is limited by its severe systemic toxicity. We found that human cells transfected with vectors encoding TNF without the TACE cleavage site (DTACE-TNF) still released functional cytokine at substantial levels that varied between transfected cell lines of different tissue types. Vectors enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Recently, it was found that the TNFα mutation on ADAM-17 cleavage site was not enough to prevent cleavage and secretion of TNFα. To avoid the effect of secretory TNFα effect completely, Kipps and colleagues expressed a chimeric protein with extracellular domain of TNFα and transmembrane stalk portion of CD154 using adenovirus vector system and tested its antitumor activity ( 27 ). The systemic toxicity was not seen with the adenovirus vector expressing TNFα-CD154 chimera.…”
Section: Tumor Therapy Using Membrane-bound Form Of Tnfαmentioning
confidence: 99%
“…Recently, it was found that the TNFα mutation on ADAM-17 cleavage site was not enough to prevent cleavage and secretion of TNFα. To avoid the effect of secretory TNFα effect completely, Kipps and colleagues expressed a chimeric protein with extracellular domain of TNFα and transmembrane stalk portion of CD154 using adenovirus vector system and tested its antitumor activity ( 27 ). The systemic toxicity was not seen with the adenovirus vector expressing TNFα-CD154 chimera.…”
Section: Tumor Therapy Using Membrane-bound Form Of Tnfαmentioning
confidence: 99%
“…On the basis of these assumptions, this type of modified cytokine gene therapy has been reported on interleukin-2, 13,19,20 interleukin-12, 21 fractalkine (CX3CL1) 22 and TNF. 23 Indeed, accumulating evidence revealed that the membrane-bound form of cytokine genes can exhibit more antitumor effects than the corresponding soluble ones. Likewise, the current study confirms that the membrane-bound form of MCP-1 can attract more immune cells, including monocytes/macrophages and T lymphocytes, to the tumor sites and can induce the expression of TNF.…”
Section: Discussionmentioning
confidence: 99%
“…To check this possibility, we chose Mab1 as a capture antibody. Mab1 is a monoclonal antibody against hTNF-a and is widely used as a capture antibody in a sandwich immunoassay together with biotinylated Mab11 as a detection antibody [33]. We optimized the assay conditions with respect to the concentrations of the capture antibody and rB3-mAP fusion protein, and observed that 2 mg mL À1 of Mab1 and 2 mg mL À1 of rB3-mAP fusion protein led to the best assay performance.…”
Section: Sandwich Immunoassay Using Repebody-map Fusion Proteinmentioning
confidence: 98%